Avaliação dos parâmetros psicomotores de equilíbrio e coordenaçao motora apendicular em crianças obesas - Encarnação, Gislaine Aparecida Alves da [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Obesity is a growing problem all over the world, reaching all age groups and social categories. This is a concern ing fact, because the current life style, more and more sedentary, favors the develop of this disease. Children suffer with this ill more and more prematurely and many of its consequences will be carried during all their lives. With the intention of better understand the relationship between obesity and children's motor development, the present research investigated, through psychomotor evaluations of equilibrium and appendicular motor coordination, based on the Exame Neurológico Evolutivo (ENE), the existence of changes in the performance of this variables in obese children and children with normal weight, in their first year on fundamental education in a public state school. The static equilibrium presented itself lower than normal in obese, compared to the normal weight group. Statistically significant differences were not found in respect to dynamic equilibrium and appendicular motor coordination. With that, we can conclude that the static equilibrium suffered influence of obesity, because the centre of gravity might have been changed due to excessive weight

A obesidade é um problema crescente em todo o mundo, atingindo todas as faixas etárias e classes sociais. Esse é um fato preocupante, pois o estilo de vida atual, cada vez mais sedentário, favorece o desenvolvimento dessa doença. As crianças sofrem com esse mal cada vez mais precocemente e muitas de suas consequências serão carregadas por toda a sua vida. Com o intuito de melhor compreender a relação entre a obesidade e o desenvolvimento motor infantil, a presente pesquisa investigou, por meio de avaliações psicomotoras de equilíbrio e coordenação motora apendicular, baseadas no Exame Neurológico Evolutivo (ENE), a existência de alterações no desempenho destas variáveis em crianças obesas e com peso normal, ingressantes no ensino fundamental de uma escola pública estadual. O equilíbrio estático se apresentou abaixo do normal nos obesos, comparados ao grupo com peso normal. Não foram encontradas diferenças estatisticamente significantes no que se refere ao equilíbrio dinâmico e da coordenação motora apendicular. Com isso, podemos concluir que o equilíbrio estático sofreu influência da obesidade, pois o centro de gravidade pode ter sido alterado devido ao excesso de peso
Keywords: Psicomotricidade; Obesidade nas crianças; Equilibrio (Fisiologia); Movement, Psychology of